A Communication-assisted Scheme in Radial Distribution Systems Using Phasor Measurement Units - Jain, A.; Verma, M.K. (Taylor and Francis Ltd., 2020)
Automation of the distribution system may be an essential requirement in the smart grid architecture. In this paper, the architecture of the distribution system has been proposed, where Phasor Measurement Unit (PMU) has been placed at the main substation receiving supply from the grid through the incoming feeder, as well as at all distribution transformers (DTs). PMU installed at the main substation is linked to master controller through IEC 61850. PMUs placed at DTs are connected to the corresponding local controller through the IEC 61850. Estimated voltage and current phasors together with frequency are transmitted from PMU to the local controller through IEC 61850 communication protocol. Controllers perform different tasks based on the data received from PMUs. Each local controller is linked to master controller as well as to all smart meters placed at loads supplied by the DT. Bidirectional exchange of information takes place between master and local controllers as well as between local controller and smart meter. PMUs are also linked with the smart meters using PLC communication link. In this paper, information about the available power at the substation and at the distribution transformer is developed in real-time with the help of PMU by considering the load disconnection/connection based on available power (from time t = 0.56sec to time t = 0.75sec), protection of feeder against overcurrent (from time t = 0.15sec to time t = 0.20sec), and power theft detection and elimination (from time t = 0.21sec to time t = 0.23sec) through eMEGASim® OP5600 OPAL-RT real-time simulator. © 2019 IETE.
Keywords: Available power loss; distribution system; IEC 61850; phasor measurement unit (PMU); protocol; smart metering